Reduction Of Chromite Ore At Different Flow Rates Of Inert Gas - Dolly Chakraborty; S. Ranganathan; S. N. Sinha (The Southern African Institute of Mining and Metallurgy, 2007)
Pre-reduction of chromite outside the submerged-arc furnace (SAF) can significantly lower the specific power consumption in the SAF process. Conventional processes for the pre-reduction of the ore operate at relatively high temperatures, at 1400-1500°C. It is possible to enhance the rate of reduction at low temperatures by optimizing the flow rate of inert gas over the reaction site. The influence of the flow rate of inert gas on the rate of reduction of chromite ore was investigated. The rate of reduction initially decreased wit the flow rate of the gas. It increased subsequently at higher flow rates to be followed by a decrease again. There was an optimum flow rate at which maximum reduction could be obtained. It was possible to achieve high levels of reduction at 1200°C by optimising the flow rate of the gas. The degree of reduction obtained was comparable to that obtained at 1400-1500°C, by conventional process routes.